Indoor Environmental Quality (IEQ) in Healthcare Settings and Cognitive Performance of Staff: The Role of Ventilation, Microclimate and Sensory Load for Medical Education and Patient Safety – a Narrative Review - Karol, Michał; Koseska, Kamila; Borowicz, Jan; Górecki, Bartosz; Kloch, Kinga; Romaniuk, Patryk; Lohin, Mariia-Khrystyna; Strawińska, Aleksandra; Bednarczyk, Małgorzata (Journal of Education, Health and Sport, 2026)
Introduction. Clinical work is performed under conditions of high cognitive load, time pressure and frequent interruptions. Research on patient safety has traditionally focused on sleep deprivation, fatigue and work organisation, whereas environmental factors are analysed less frequently, despite their chronic and cumulative effects. Aim. The aim of this narrative review is to present the current state of knowledge on the relationship between indoor environmental quality (IEQ) and cognitive performance of healthcare professionals and trainees, and to discuss the implications of these associations for medical education and patient safety. State of knowledge. IEQ encompasses ventilation and air quality, thermal and humidity conditions, lighting, and sensory load, including noise. Experimental and observational evidence suggests that even moderate deviations of environmental parameters may be associated with impairments in vigilance, attention, working memory, reaction time and executive functions, particularly when combined with sleep deficit, multitasking and high distraction. Indirect effects may also arise from exposures typical of hospital environments and from factors increasing respiratory discomfort and communication burden. Conclusions. Framing IEQ within a human factors perspective supports a systems-based approach to quality and safety. Monitoring environmental parameters and implementing low-cost organisational interventions may represent a practical component of strategies aimed at supporting cognitive performance of staff and the effectiveness of medical education.